Cyclic thiatetraynes: syntheses and structural properties - Rausch, Bernhard J.; Werz, Daniel B.; Rittinger, Stefan; Gleiter, Rolf; Oeser, Thomas; Rominger, Frank (Perkin, 2002)
The syntheses of three cyclic dithiatetraynes 4-6 with the sulfur atoms in propargylic positions are reported. Their structural features have been studied by means of X-ray analysis on single crystals. Additionally, six cyclic octathiatetraynes 15-20 with sulfur atoms in α,α′-positions to the triple bond have been prepared. The structures of 15 and 17 have been elucidated by means of X-ray analysis. These macrocycles exhibit an ellipsoidal geometry dominated by the stiff triple bond moieties. In the case of 4 a three-dimensional columnar structure is found, demonstrating the unique features of the potential cavities.